CONSTITUTIVE EXPRESSER OF PATHOGENESIS-RELATED GENES 5 is an RNA-binding protein controlling plant immunity via an RNA processing complex. Issue 5 (8th February 2022) - Peng, Shun; Guo, Dongbei; Guo, Yuan; Zhao, Heyu; Mei, Jun; Han, Yakun; Guan, Rui; Wang, Tianhua; Song, Teng; Sun, Keke; Liu, Yunhan; Mao, Ting; et al.
Abstract: Plant innate immunity is capable of combating diverse and ever evolving pathogens. The plasticity of innate immunity could be boosted by RNA processing. Arabidopsis thaliana CONSTITUTIVE EXPRESSER OF PATHOGENESIS-RELATED GENES 5 (CPR5), a key negative immune regulator, is a component of the nuclear pore complex. Here we further identified CPR5 as a component of RNA processing complexes. Through genetic screening, we found that RNA splicing activator NineTeen Complex and RNA polyadenylation factor CLEAVAGE AND POLYADENYLATION SPECIFICITY FACTOR, coordinately function downstream of CPR5 to activate plant immunity. CPR5 and these two regulators form a complex that is localized in nuclear speckles, an RNA processing organelle. Intriguingly, we found that CPR5 is an RNA-binding protein belonging to the Transformer 2 (Tra2) subfamily of the serine/arginine-rich family. The RNA recognition motif of CPR5 protein binds the Tra2-targeted RNA sequence in vitro and is functionally replaceable by those of Tra2 subfamily proteins. In planta, it binds RNAs of CPR5-regulated alternatively spliced genes (ASGs) identified by RNA-seq. ARGONAUTE 1 ( AGO1 ) is one of the ASGs and, consistent with this, the ago1 mutant suppresses the cpr5 phenotype. These findings reveal that CPR5 is an RNA-binding protein linking RNA processing with plant immunity. Abstract : CPR5 is an RNA-binding protein of the SR family and modulates plant immunity via an RNA processing complex.